Use of Ozone Therapy and Thymoquinone in the Prevention of Formaldehyde Toxicity by Inhalation: An Experimental Study - Aksu, Feyza; Kavakli, Ahmet; Kuloglu, Tuncay; Yilmaz, Seval; Kaya, Emre; Akkoc, Ramazan Fazil; Ogeturk, Murat (Springernature, 2024)
Introduction: The study determined the damage caused by formaldehyde (FA) exposure in blood and liver samples using biochemical markers. Histopathological analysis was performed using the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) method and measurement of CD68 cell density. To what extent the antioxidant molecules thymoquinone (TQ) and ozone (O-3) reversed the damage caused by FA exposure was investigated, both when used alone and combined. Methods: Fifty-six Sprague-Dawley male rats of eight to ten weeks of age were used in the experiment. The rats were divided into eight groups, with seven rats in each group: the untreated control group, the group treated with TQ (10 mg/kg/day), the group treated with O-3 (150 mu g/kg/day), the group treated with TQ+O-3, the group exposed to FA (10 ppm 8 h/day), the group receiving FA+TQ, the group receiving FA+O-3, and the group receiving FA+TQ+O-3. Serum aspartate transaminase (AST), alanine transaminase (ALT), total antioxidant (TAS, U/mL), and total oxidant (TOS, nmol/mL) levels were analyzed. TAS and TOS levels, CD68 cell density, and apoptotic cells were determined in liver tissues. Results: FA exposure caused an increase in serum AST and ALT levels of (p<0.05) experimental animals, a decrease in TAS levels in serum (p=0.03) and liver (p>0.05) and an increase in TOS levels (p>0.05), TUNEL positivity (p<0.001), and CD68 cell density (p=0.004). Administration of TQ and O-3 as antioxidants significantly reversed biochemical and histopathological alterations in the serum and liver. Conclusion: TQ and ozone therapy suppressed oxidative stress caused by FA exposure and reversed the emerging histopathological deteriorations. Ozone therapy did not suppress the effects of TQ. Therefore, ozone therapy can be given as a supportive therapy along with the main therapeutic agents. We think TQ and ozone therapy may be useful to protect individuals exposed to FA.
Keywords: tunel; ozone therapy; thymoquinone; liver; formaldehyde exposure